Characterization of tin oxide (SnO2) nanostructures prepared by thermal oxidation - Nuraini, Abdullah; Noor Mazni, Ismail; Dewan Muhammad, Nuruzzaman (American Institute of Physics Inc., 2018)
Tin oxide (SnO2) nanocrystals and nanowires were successfully synthesized on Si(100) substrate by thermal oxidation method at different oxidation temperatures 450oC, 500oC and 550oC. The synthesized nanostructures were characterized by FESEM, Uv-Vis and Photoluminescence spectrum. The morphology of the samples was confirmed by FESEM and the optical properties were obtained from Uv-Vis and photoluminescence (PL) spectrum. Tin oxide nanocrystals were obtained at oxidation temperatures 450oC and 550oC. However, at 500oC, tin oxide nanowires were obtained. The energy band gaps of tin oxide nanocrystals at 450oC and 550oC were 1.35eV and 1.25eV respectively and energy band gap of tin oxide nanowires at 500oC was 1.21eV. PL emission spectra results showed that tin oxide nanocrystals at 450oC exhibit maximum emission at 775nm (1.60eV) at first maximum peak and 815nm (1.52eV) at second maximum peak while tin oxide nanowires at 500oC exhibit first maximum peak at 450nm (2.76eV), second maximum peak at 500nm excitation (2.48eV) and third maximum highest peak at 650nm excitation (1.91eV).